Development of the implementation of public information disclosure by regional governments in Indonesia: a systematic literature review - Irsyadinnas Irsyadinnas; Sinta Ningrum; Centurion Chandratama Priyatna (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
One of the characteristics of a democratic country is an open government. The administration of the state can take place in democratic and open governance if it applies the principle of public information disclosure (PID) in the administration of its government. In this regard, the Government of Indonesia issued Law Number 14 of 2008 concerning the Openness of Public Information, which must be implemented by all public bodies at every level of government in Indonesia, starting from the central government, and provincial governments, to district/city governments. This study's purpose is to see the extent to which the development of PID implementation practices is at the local government level. The method used in this research is a systematic literature review (SLR) method, by collecting all the results of the latest study on implementing PID at the local government level in Indonesia and systematically analyzing them. From 674 published articles obtained from the scholar.google.com portal using the Publish & Perish application, a PRISMA flow diagram was carried out so that 69 reports were received that were directly related to implementing KIP in local governments in Indonesia. The results show that the quality of PPID institutions influences the implementation of KIP in local governments, the availability of legal umbrellas in the form of regional regulations and head regulations, the information media used, and the available public information according to general needs.